High Sensitivity Of Nanocrystalline SnO2-Y2O3 Thin Films Based UV-Detector Prepared Using Chemical Bath Deposition (Journal of the College of Basic Education, 2024)
Nanocrystalline Tin dioxide - Yttrium oxide (NC SnO2-Y2O3) thin film was effectively created by employing the chemical bath deposition approach on SiO2/Si substrates. X-ray diffraction, field emission scanning electron microscopy [FESEM], and energy-dispersive X-ray spectroscopy were used to analyze the structural and the surface morphology of the annealed sample at 500°C for two hours in air. When annealed at 500°C, the SnO2-Y2O3 film crystallized was accomplished with a tetragonal rutile structure. The nanocrystalline SnO2 thin film was effectively employed as a UV photodetector device (UV PDs). A UV photo detector based on nanocrystalline SnO2-Y2O3 film showed 2988% sensitivity when exposed to a 360 nm wavelength (6 mW/cm2) at an applied voltage of 3 V. In contrast, the responsivity value was 3.247 A/W. The rise and full times were determined by calculating to be 0.663 s and 0.436 s, respectively. The excellent performance of the device could be correlated with high surface-to-volume proportions including its elevated crystal performance. Given its outstanding stability and reliability, the nanocrystalline SnO2-Y2O3 thin film sensor is the optimum option for commercially photo-electronic applications.